Antitumor activity of lycorine in renal cell carcinoma ACHN cell line and its mechanism - Huang, Yi-Qiang; Zhang, Yi-Ming; Jin, Zhong; Li, Xie-Zhao; Wang, Chong-Shan; Xu, Kai; Huang, Peng; Liu, Chun-Xiao (Nan fang yi ke da xue xue bao = Journal of Southern Medical University, 2016)
To investigate the antitumor effect of lycorine on renal cell carcinoma ACHN cells and explore the possible mechanism. We used flow cytometry to examine the effect of lycorine on ACHN cell cycle and apoptosis. The cell proliferation, migration and invasion were assessed with MTS assay, wound healing assay, and Transwell assay, respectively. Colony forming assay was performed, and the mRNA and protein levels of Bax, Bcl-2, survivin, caspase-3, cyclin D1 and CDK4 were measured with qRT-PCR and Western blotting. Lycorine obviously inhibited the proliferation of ACHN cells with an IC(50) of 24.34 µmol/L. Lycorine also induced apoptosis of ACHN cells, caused cell cycle arrest at G(0)/G(1) phase, and suppressed the colony forming ability of the cells in a dose-dependent manner. The migration and invasion of ACHN cells were significantly inhibited by 5 µmol/L lycorine. Lycorine up-regulated the mRNA levels of CDK4, Bax, caspase-3 while down-regulated the levels of survivin, Bcl-2 and Cyclin D1; the protein levels of